Watery Romanticism: Walking and Sailing West with Keats - Connolly, Claire (Romanticism on the Net)

(untitled) (Université de Montréal, 2022)
This article explores the meanings of John Keats’s short-lived trip across the Irish sea in the summer of 1818. His encounters with Scottish and Irish coasts were shaped by a rapidly changing travel infrastructure, including roads, bridges, and harbours. They also resulted in a remarkably vivid description of an impoverished Irish woman whose body and presence challenge romantic aesthetics while also calling up a more contingent, watery Romanticism.